MINERALOGY AND ORGANIC MATTER CONTENT OF BOTTOM ASH SAMPLES FROM AGIOS DIMITRIOS POWER PLANT, GREECE - Kantiranis, N.; Georgakopoulos Α.; Fiiippidis, A.; Drakoulis, A. (Bulletin of the Geological Society of Greece, 2004)
Four bottom ash samples from the Power Units of the Agios Dimitrios Power Plant were studied by the method of PXRD to determine their semi-quantitative mineralogical composition. Their organic matter content was calculated by a wet chemical process. Also, the loss on ignition was measured. The samples are constituted mainly of calcite, quartz and feldspars, while micas, clays, gehlenite and portlandite were determined in a few samples in smaller quantities. The amorphous material varied between 10-43 wt. %, while organic matter varied between 5-42 wt. %. Measurements of the loss on ignition overestimate the unburned lignite contents in the bottom ash samples. The management of bottom ashes with high contents of unburned lignite should differ to that of the fly ashes. The oxidation of the inorganic compounds of the unburned lignite may lead to environmental degradation of the landfill areas. Samples showing lower values of organic matter are suitable for a series of uses, such as: snow and ice control, as an aggregate in lightweight concrete masonry units,as a raw feed material for portland cement, as an aggregate in cold mix emulsified asphalt mixes, base or sub-base courses, or in shoulder construction. Systematic study of the unburned lignite of bottom ashes is needed for possible re-combustion.